2012
DOI: 10.1111/j.1574-6941.2012.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and survey of novel fluoroacetate-degrading bacteria belonging to the phylum Synergistetes

Abstract: Microbial dehalogenation of chlorinated compounds in anaerobic environments is well known, but the degradation of fluorinated compounds under similar conditions has rarely been described. Here, we report on the isolation of a bovine rumen bacterium that metabolizes fluoroacetate under anaerobic conditions, the mode of degradation and its presence in gut ecosystems. The bacterium was identified using 16S rRNA gene sequence analysis as belonging to the phylum Synergistetes and was designated strain MFA1. Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 62 publications
2
60
0
Order By: Relevance
“…Preliminary biochemical characterization of strain MFA1 was reported by Davis et al [19], but further investigation of the factors that influence its survival and growth in gut ecosystems is required. The primary aim of this study was to investigate the nutritional requirement of strain MFA1 with an emphasis on amino acid and peptide utilization under various culturing conditions, which may facilitate the establishment and maintenance of strain MFA1 in the rumen.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Preliminary biochemical characterization of strain MFA1 was reported by Davis et al [19], but further investigation of the factors that influence its survival and growth in gut ecosystems is required. The primary aim of this study was to investigate the nutritional requirement of strain MFA1 with an emphasis on amino acid and peptide utilization under various culturing conditions, which may facilitate the establishment and maintenance of strain MFA1 in the rumen.…”
Section: Introductionmentioning
confidence: 95%
“…This bacterium is asaccharolytic and ferments amino acids for growth [19], which are characteristics shared across the Synergistetes phylum [6]. Moreover, strain MFA1 is capable of anaerobically degrading fluoroacetate, a toxic compound found in some Acacia plant species and heartleaf (Gastrolobium spp.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schröder (2003) and Meesters and Schröder (2004) reported that PFOA was degraded under anaerobic conditions using activated sludge in a sewage treatment plant, but the degradation efficiency was low. There are many other reports on the bacterial degradation of PFCs such as fluorobenzene (Carvalho et al, 2005), fluoroanilin (Amorim et al, 2013), PFB (Hughes et al, 2011), fluoroacetate (Davis et al, 2012), perfluorohexylethanol (Dinglasan et al, 2004;Wang et al, 2009;Liu et al, 2010) and perfluorohexylsulfonate (Wang et al, 2011). Some naturally occurring microorganisms possess defluorinating enzymes that attack the C-F bond.…”
Section: Introductionmentioning
confidence: 99%